DEMOCRATIC LEADERSHIP STYLE IN ORGANIZATIONS PUBLIC HEALTH CARE SERVICES - Feni Sulistyawati; Ambika Kurnia Mustikawati; Ni Luh Purnama Yanti (Jurnal Delima Harapan, 2023)
Achieving good basic health status requires quality and affordable PHC health service organizations that are influenced by the abilities and skills of health workers. Leaders are figures who play a role in the formation of quality health workers. The majority of leaders in health care organizations apply a democratic leadership style in leading their members. This article aims to determine the effectiveness of implementing a democratic leadership style in the management of health center organizations. This study uses a literature review of nine articles that meet the initial screening criteria. The leadership styles that are often applied in PHC are laissez-faire, participative, delegative, instructional, and democratic. The democratic leadership style in decision making prioritizes deliberation but focuses less on the right decision and more on the preferred decision The application of democratic leadership style has an effect on increasing motivation, performance, employee satisfaction, optimal health service quality and providing service satisfaction to patients, but is less able to improve employee discipline and health service coverage.